A Computer Component Recognition Application (OAK STALL 1.0) Using Augmented Reality Technology - -, Estu sinduningrum (PETIR, 2024)
Augmented Reality (AR) technology has been widely implemented in various fields, one of which is education. The results of the initial questionnaire to the students who had been conducted obtained information that the learning process in the Computer Architecture Organization (OAK) course at UHAMKA in the Informatics Engineering (IT) study program currently still uses the usual (conventional) method which is still applied at 94.42%. considered less attractive. In the OAK course, 93.69% of students stated that they only provided material without practice, while 94.17% of students stated that they needed an AR application to help understand computer component material. The results of the questionnaire 85.44% stated that the computer components that needed to be made AR included development history: Processor, RAM, Harddisk, and CPU, which could make it easier for students to understand and arouse students’ motivation to learn. Therefore, the learning process in OAK lesson, namely the introduction of computer components requires new learning media such as AR technology to visualize computer components in 3D or animation to increase student learning attractiveness and easy to understanding.